Introduction to Specialty (Management) - Krasnokutska, N. S. (NTU "KhPI", 2018)
These lecture slides contain summarized notes concerning the course "Introduction to Specialty (Management)". The slides give the basic information of the higher education system, presents the brief explanation of management as a science and profession, explains the management roles and competencies.

Представлений конспект лекцій у слайдах містить узагальнені матеріали з курсу "Вступ до спеціальності "Менеджмент". У слайдах представлена базова інформація щодо системи вищої освіти, розкриті особливості менеджменту як науки та професії, визначені основні управлінські ролі та компетенції.
Вступ до спеціальності (Менеджмент)
Keywords: management; higher education; managers; bologna process; management roles; management competencies